(untitled) (Biological Sciences - PJSIR, 2000)
Benzimidazo [1. 2-a 1benzimadozoles (1, R=H) were synthesized by the trialkylphosphite-induced deoxygenation and thermolysis of l-o-nitrophenyl and l-o-azidophenyl benzimidazole. Spectral and other properties of the product and the intermediate compounds are reported.